A Comparative Review of (RT-PCR) And Next-Generation Sequencing (NGS) in Plant Virus Diagnostics: Methodological Insights, Practical Applications, and Future Directions - Al-KAEATH, Nabeel (American Journal of Biology and Natural Sciences, 2025)
Next-Generation Sequencing (NGS) and Reverse Transcription Polymerase Chain Reaction (RT-PCR) have become two of the most significant molecular instruments in the area of plant virology. Compared to NGS, which offers a comprehensive and unbiased analysis of the viral plant virome, RT-PCR only gives quick and sensitive detection of well-characterized viral pathogens, making it easier to discover novel viruses and to evaluate genetic diversity and evolution. In this review, peer-reviewed articles have been analyzed in a systematic manner (published since 2010 and up to 2024) to assess the methodological basis, diagnostic accuracy, and clinical implication of the two methods. Also, recent practical research findings carried out in Iraq are added to give a regional opinion on the feasibility of implementation. Its results suggest that the RT-PCR-plus-NGS approach is more accurate and flexible in terms of diagnosis, especially in resource-limited environments. The review highlights the need to integrate hybrid diagnostic approaches to facilitate the current plant virus surveillance and disease management initiatives.